Alternate-day, low-dose aspirin and cancer risk: long-term observational follow-up of a randomized trial - Cook, Nancy R; Lee, I-Min; Zhang, Shumin M; Moorthy, M Vinayaga; Buring, Julie E (Annals of internal medicine, 2013)
Recent evidence suggests that daily aspirin use decreases cancer risk, particularly for colorectal cancer, but evidence for alternate-day use is scant. To examine the association between long-term, alternate-day, low-dose aspirin and cancer in healthy women. Observational follow-up of a randomized trial. Female health professionals. 39,876 women aged 45 years or older in the Women's Health Study (ClinicalTrials.gov: NCT00000479), 33 682 of whom continued observational follow-up. 100 mg of alternate-day aspirin or placebo through March 2004, with a median 10-year follow-up. Posttrial follow-up continued through March 2012. Cancer incidence. A total of 5071 cancer cases (including 2070 breast, 451 colorectal, and 431 lung cancer cases) and 1391 cancer deaths were confirmed. Over the entire follow-up, aspirin had no association with total (hazard ratio [HR], 0.97 [95% CI, 0.92 to 1.03]; P = 0.31), breast (HR, 0.98 [CI, 0.90 to 1.07]; P = 0.65), or lung (HR, 1.04 [CI, 0.86 to 1.26]; P = 0.67) cancer. Colorectal cancer was reduced in the aspirin group (HR, 0.80 [CI, 0.67 to 0.97]; P = 0.021), primarily for proximal colon cancer (HR, 0.73 [CI, 0.55 to 0.95]; P = 0.022). The difference emerged after 10 years, with a posttrial reduction of 42% (HR, 0.58 [CI, 0.42 to 0.80]; P < 0.001). There was no extended effect on cancer deaths or colorectal polyps. More gastrointestinal bleeding (HR, 1.14 [CI, 1.06 to 1.22]; P < 0.001) and peptic ulcers (HR, 1.17 [CI, 1.09 to 1.27]; P < 0.001) occurred in the aspirin group. Not all women received extended follow-up, and posttrial ascertainment bias cannot be ruled out. Gastrointestinal bleeding, peptic ulcers, and polyps were self-reported during extended follow-up. Long-term use of alternate-day, low-dose aspirin may reduce risk for colorectal cancer in healthy women.